Factors Affecting the Need to have Accounting Technical Competence, Professional Skills and Professional Values, Ethics, and Attitudes – The Case of Thailand - Sarapaivanich, Naruanard; Trakarnsirinonta, Worraphan; Laohavisudhi, Suvanna; Viriyachinkarn, Tanikan (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper Research aims: This study aims to examine the factors affecting accounting professionals’ essential skills as specified by the International Education Standards (IESs). Design/Methodology/Approach: The antecedent factors are drawn from Aldefer’s (1969) theory of existence, relatedness and growth needs (ERG). A mixed method approach involving auditors, standard setters and faculty members is employed in this study. Research findings: The results suggest that accounting professional skills are motivated by the growth and relatedness needs. The findings further reveal that the length of accounting training experience and the students’ intention to work in accounting fields, after graduation, are key factors which enhance their accounting technical competence. Theoretical contributions/Originality: This study contributes to the emergent interest in this field by focussing on how the ASEAN Economic Community (AEC) members like Thailand, responds to the needs of the IES. The ERG theory could be adapted in understanding the factors affecting the development of accounting technical competence, professional skills and professional values, ethics and attitudes. Practitioner/Policy implications: The ERG theory assists managers in recognising that if growth opportunities are not furnished to employees, they may regress to relatedness needs. The findings thus suggest that in order to develop students’ accounting technical skills (IES2), the academic institutions should encourage students to participate in accounting training programmes as a part of the course curriculum. The results further indicate that accounting professional skills (IES3) can be enhanced if they get acceptance from their superiors and co-workers. Research limitations: The samples of this paper comprise accounting students from northern Thailand. Only three International Education Standards (IESs) which are implemented in Thailand are examined. Keywords: Accounting Technical Competence, Professional Skills, Professional Values, Ethics and Attitudes JEL Classification: M41, M48